An Ordinance to Prevent the Firing of Guns, and Running of Horses, §§ 1-2, in The Arkansas Advocate, Mar. 7, 1832, at 4 - (:unkn) unknown (My University, 1832)
§Be it ordained by the Mayor and Town Council of the town of Little Rock, That if any free person shall wantonly fire or shoot off any gun, pistol, or other fire arms, within the bounds of the corporation of the town of Little Rock; or if any person shall run, gallop or canter, any horse, mare, gelding, mule, jack or jenny, through any of the public squares, streets or alleys, of said town, he or she, if free, shall on conviction before the Mayer of the town, forfeit and pay for each offence a sum not exceeding§ten dollars, and shall moreover stand committed until the same be paid together with the attendant costs; and if a slave be guilty of any of the above offences, he or she shall, for each offence, receive on his or her bare back,§ten§stripes or lashes, to be well laid on by the town constable.
Keywords: DISCHARGE